Analisis faktor internal dan eksternal pengembangan perkebunan rakyat kopi Arabika di Kabupaten Pegunungan Arfak Provinsi Papua Barat - Antonius Suparno; Aser Rouw; Diana Irbayanti; Linda Ernawati Lindongi; Hangrie Jemmy Namserna (Agrotek, 2022)
Arfak Mountains Regency is part of West Papua Province with an undulating to mountainous topography that spreads at an altitude of 800 – 3,000 m above sea level with the main livelihood of its community is farming highland vegetables. This region has a very suitable and potential climate for the development of Arabica coffee. Arfak Mountains Regency also has 2 lakes at an altitude of 2000 m above sea level, so the existence of coffee plantations can support the development of ecotourism in this area. The development of community coffee plantations is not as good as cocoa plantations. This is presumably due to the difficulty of the transportation of marketing results in the past. However, in line with the current infrastructure development, regional development progress, and the growth in the coffee economic value, the development of coffee plantations based on community plantations require significant attention. To be more focused on the development of arabica coffee in the Arfak Mountain Regency, it is necessary to be attentive to internal and external factors as the basis of policy making. This study aims to analyze internal factors (IFE) and external factors (EFE) in coffee farming communities in Anggi Gida District and Anggi Giji District. The results of the IFE and EFE analysis show that farmers in Anggi Giji District have more opportunities (quadrant I: 2.79;2.79) to develop coffee than farmers in Anggi Gida District (quadrant I: 2.61; 2.25). Based on the SWOT analysis both in Anggi Gida District and in Anggi Giji District, the development of Arabica coffee community plantations must implement a strategy to optimize land (S1, S2, O2, O3, O4), improve technical skills (W3, O1, O2, O4), optimize farmer group institutions (S3, S4, T1, T2, T3, T4), and open a marketing network (W2, T3, T4).